2020
DOI: 10.1073/pnas.1918172117
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in DNA methylation homeostasis and the emergence of epialleles

Abstract: In plants and mammals, DNA methylation plays a critical role in transcriptional silencing by delineating heterochromatin from transcriptionally active euchromatin. A homeostatic balance between heterochromatin and euchromatin is essential to genomic stability. This is evident in many diseases and mutants for heterochromatin maintenance, which are characterized by global losses of DNA methylation coupled with localized ectopic gains of DNA methylation that alter transcription. Furthermore, we have shown that ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 105 publications
0
68
1
Order By: Relevance
“…These results also reflect the rarity at which epimutations linked to morphological variation are found in the laboratory and/or field [ 27 – 31 , 33 ]. One emerging hypothesis is that the majority of epimutations in angiosperms are byproducts of maintenance of DNA methylation associated with heterochromatin and that certain loci are more or less susceptible than others [ 45 , 46 , 56 ]. This link to maintenance processes is one commonality between the accumulation of genetic and epigenetic changes that could explain why their rates are fairly similar on a per cell division timescale.…”
Section: Discussionmentioning
confidence: 99%
“…These results also reflect the rarity at which epimutations linked to morphological variation are found in the laboratory and/or field [ 27 – 31 , 33 ]. One emerging hypothesis is that the majority of epimutations in angiosperms are byproducts of maintenance of DNA methylation associated with heterochromatin and that certain loci are more or less susceptible than others [ 45 , 46 , 56 ]. This link to maintenance processes is one commonality between the accumulation of genetic and epigenetic changes that could explain why their rates are fairly similar on a per cell division timescale.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the relationships between gene expression and methylation level are complex [ 24 , 28 , 50 , 51 ]. Correlation may switch from positive to negative values according to environmental variations such as recently described in palm roots exposed to high salinity [ 52 ].…”
Section: Results and Discussionmentioning
confidence: 99%
“…Accordingly, the methylomes of 1028 natural accessions are highly variable, and many loci are polyepiallelic, meaning that they can be either unmethylated, show transposable element (TE)-like methylation (teM; mCG, mCHG, or mCHH linked to transcriptional repression), or gene body methylation (gbM; mCG normally coupled to constitutive gene expression, but also promoting the development of silenced teM alleles) [ 134 , 135 ]. Whereas TEs and sequence repeats are consistently and densely methylated by small interfering RNA (siRNA)-directed maintenance [ 133 , 136 ], the extent of gbM, in particular, differs across 725 strains and is inversely correlated with heterochromatin methylation levels through a feedback loop involving CMT3, H3K9me2, and histone turnover [ 137 ]. On the other hand, teM interacts with allele-specific gene imprinting, and it has been suggested that siRNAs contribute to epigenetic differences between strains as well [ 138 , 139 ].…”
Section: Other Sources Of Regenerative Variationmentioning
confidence: 99%
“…In addition to DNA methylation, it was reported that H3K27me3 levels show allele-specific inheritance, but only a few targets differ between Col and L er strains, which has been coupled to the spreading of repressive heterochromatin marks (e.g., H3K9me2) from nearby TE insertions [ 142 ]. Although the underlying mechanisms are not straightforward, variable methylation and histone modification patterns amplify transcriptomic variation, underlined by differential expression of 22,085 genes among 998 natural accessions, which further drives phenotypic variation and adaption [ 134 , 135 , 137 , 142 ]. Transcriptome-wide association studies (TWAS) could be applied to identify eQTLs for de novo shoot organogenesis.…”
Section: Other Sources Of Regenerative Variationmentioning
confidence: 99%